Outcome after Surgery of Lumbar Spinal Stenosis: A Randomized Comparison of Bilateral Laminotomy, Trumpet Laminectomy, and Conventional Laminectomy - Haddadi, Kaveh; Ganjeh Qazvini, Hamid Reza (Frontiers in Surgery, 2016)
Background: laminectomy is the traditional operating method for the decompres¬sion of spinal canal stenosis. New partial decompression processes have been suggested in the treatment of lumbar stenosis. The benefit of a micro surgical approach is the chance of an extensive bilateral decompression of the spinal canal or foramen at one or numerous levels, through a minimal para-spinal muscular separation. Purpose: to match the safety and the clinical consequences after a bilateral laminotomy, laminectomy and trumpet laminectomy in patients with lumbar spinal stenosis who were randomized to one of three treatment groups. Study design: prospective study Methods: One hundred and twenty consecutive patients with 227 levels of lumbar stenosis without significant herniated discs or instability were randomized to three treatment groups (bilateral laminotomy [Group 1], laminectomy [Group 2] and trumpet laminectomy [Group 3]). Perioperative parameters and complications were documented. Symptoms and scores, such as a visual analog scale (VAS), Oswestry Disability Index and patient satisfaction were assessed preoperatively and at 3, 6, and 12 months after surgery. Adequate decompression was achieved in all patients on the basis of surgeon satisfaction. Results: The global complication rate was lowest in patients who had undertaken bilateral laminotomy (Group 1). The minimum follow up of 12 months was achieved in 100% of patients. Matched with that experience in Group 1, but, with more remaining back and leg pain was found in Group 2, 3.85 ± 0.28 and 1.60 ±0.44 respectively and 3.24± 0.22 and 2.44 ±0.26 in Group 3 respectively compared with 1.84±0.28 and 1.25 ±0.12 (Group 1) at the one year follow-up assessment (p < 0.05). It was the same for the ODI scores, which reached 14 ±8 % (Group 1), 28 ±12 % (Group 2), and 26±16 after 12 months of surgery (Group 3) (significant, p < 0.01 compared with preoperative scores). Patient satisfaction was higher in Group 1, with 7.5, 20, and 25% of patients displeased (in Groups 1, 2, and 3, respectively; p< 0.01). Conclusion: Bilateral Laminotomy is certified acceptable and harmless in decompression of lumbar stenosis, causing a highly significant decrease of symptoms and disability